Exploring saving behaviour of pre-degree students: a study of Universiti Teknologi MARA Selangor Dengkil Campus / Siti Khadijah Omar, Marziah Mokhtar and Azlin Shafinaz Arshad - Omar, Siti Khadijah; Mokhtar, Marziah; Arshad, Azlin Shafinaz (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2019)
The purpose of this paper is to explore the saving behaviour of pre-degree students. The determinants adopted in this study are financial literacy, parental socialization, peer evaluation and self-control using Theory of Planned Behaviour (TPB). This study uses quantitative approach where survey questionnaire was distributed using stratified random sampling to pre- degree students studying at Centre of Foundation Studies, Universiti Teknologi MARA, Dengkil Campus. A total of 300 questionnaires were distributed and only 193 were deemed to be usable. The study reveals that the pre-degree students have good saving behaviour as many of the tested variables such as financial literacy, parental socialization, peer evaluation and self- control were all positive especially for parental socialization. The study provides some insights on the saving behaviour of pre-degree students and factors that influence and encourage them to save.